2007
DOI: 10.1227/01.neu.0000303197.87672.31
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Brachial Plexus Reconstruction After Trauma

Abstract: Statistically validated tools can be used to evaluate the quality of life, upper extremity function, and pain after brachial plexus repairs. Root avulsion injuries and delayed surgical repair correlated negatively with functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
79
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 43 publications
3
79
2
2
Order By: Relevance
“…In a previous retrospective study of patients with peripheral nerve injury, we found high DASH scores, which were associated with pain, older age, and brachial plexus injury 15 . Other studies have shown that patients with a brachial plexus injury have high levels of disability 13,58 . The results of the present study confirm previous reports that patients with upper-extremity peripheral nerve injury experience high levels of disability and that a significant predictor of higher disability is brachial plexus injury.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a previous retrospective study of patients with peripheral nerve injury, we found high DASH scores, which were associated with pain, older age, and brachial plexus injury 15 . Other studies have shown that patients with a brachial plexus injury have high levels of disability 13,58 . The results of the present study confirm previous reports that patients with upper-extremity peripheral nerve injury experience high levels of disability and that a significant predictor of higher disability is brachial plexus injury.…”
Section: Discussionmentioning
confidence: 97%
“…Authors of previous studies of outcomes following peripheral nerve injury have emphasized measures of motor and sensory recovery, data that reflect nerve regeneration and reinnervation of the motor fibers and/or sensory end organs but not the impact on the patient. More recently, investigators have recognized the importance of patient selfreport questionnaires, disability, and health-related quality of life [13][14][15]19,52 . Disability is defined as a limitation in the ability to perform tasks, activities of daily living, or other activities [53][54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors of previous studies of outcomes following peripheral nerve injury have emphasized measures of motor and sensory recovery, data that reflect nerve regeneration and reinnervation of the motor fibers and/or sensory end organs but not the impact on the patient. More recently, investigators have recognized the importance of patient selfreport questionnaires, disability, and health-related quality of life [13][14][15]19,52 .…”
Section: Discussionmentioning
confidence: 99%